Herbivore Man in Shoujo-Manga: Deconstruction of Japanese Traditional Masculinity - Nunuk Endah Srimulyani (MOZAIK HUMANIORA, 2021)
This study aims to describe soushokukei danshi, herbivorous men who represent the value of new masculinity in the girl comic series (shoujo-manga) in Japan. They are called herbivores or plant eaters because in general, their characteristics are not as dominant as the image of nikushoku or meat-eaters that is usually attached to traditional Japanese men in a patriarchal culture. To pursue the objective of this research, qualitative descriptive method and Bem Sex-Role Inventory (BSRI) theory were used with two main data from Sakura chan and Amane kun by Asazuki Norito and Monthly Girls’ Nozaki-kun by Izumi Tsubaki. Through masculinity analysis using 20 standard items of the Bem Sex-Role Inventory (BSRI) theory, it can be seen that the characteristics of herbivorous men can be found in many feminine male characters in shoujo-manga (girl comics), including not being aggressive, gentle, liking things usually synonymous with women such as dressing up, cooking, and liking sweet foods. The tendency of this kind of feminine male figure is even used as the main character of shoujo-manga. Its development even affects the fashion style and appearance of young people in daily life. In short, the herbivorous man can be considered as a deconstruction of the traditional Japanese salary-man hegemonic masculinity that emphasizes dominance, virility, and financial strength. Herbivorous men even gave birth to new masculinity values, as well as created a new economic market chance in men's cosmetics and goods.